2022
DOI: 10.1177/00375497221115734
|View full text |Cite
|
Sign up to set email alerts
|

The role of latent representations for design space exploration of floorplans

Abstract: Floorplans often require considering numerous factors, from the layout size to cost, numeric attributes such as room sizes, and other intrinsic properties such as connectivity between visible regions. Representing these complex factors is challenging, but doing so in a representative and efficient way can enable new modes of design exploration. Existing image and graph-based approaches of floorplans’ representation often failed to consider low-level space semantics, structural features, and space utilization w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The results demonstrated that the graph-based model contributes to representing, managing, and analyzing the design of building projects. Moreover, Azizi et al 23 represented the floorplan as an attributed graph with nodes and edges to reflect how people move and interact with the spaces.…”
Section: Literature Review 21 Building Fire Safety Designmentioning
confidence: 99%
“…The results demonstrated that the graph-based model contributes to representing, managing, and analyzing the design of building projects. Moreover, Azizi et al 23 represented the floorplan as an attributed graph with nodes and edges to reflect how people move and interact with the spaces.…”
Section: Literature Review 21 Building Fire Safety Designmentioning
confidence: 99%